Development of A Digital-Based Encyclopedia on Elementary School Science Content - Sylvia Lara Syaflin; Puji Ayurachmawati; Sunedi (Postgraduate, University of Mataram, 2023)
This study aims to develop a digital-based encyclopedia for elementary science content. His research and development was carried out using the Borg and Gall development procedure with 10 stages, namely: potential and problem stages, data collection, product design, design validation, design revision, product trial, product revision, feasibility trial, product revision and mass products (digital encyclopedia). The subjects of this research trial were fourth grade students at SD Negeri 162 Palembang. The results of the assessment of material experts 91%, media experts 90%, and linguists obtaining a percentage of 85.30% indicate that the digital encyclopedia being developed falls within the criteria of very valid. The results of the student response questionnaire obtained a percentage of 93.90% indicating that the digital encyclopedia being developed was included in the Very Practical criteria. So that it is suitable for use in learning